PENGUASAAN KONSEP GEOMETRI PADA SISWA SMP KOTA PONTIANAK TAHUN 2020 - Rustam, Rustam (Universitas Tanjungpura, 2021)
This research was motivated by several reasons: (1) there was a misconception of some elementary school geometry materials that were considered essential; (2) the form of evaluation given was dominantly objective/multiple choice; (3) teachers' teaching methods tend not to be contextual; and (4) students' way of thinking simply to take the practical one. Through this research, it is expected to obtain information about: geometrical reasoning in elementary schools according to Bruner's theory, problem solving and mathematical representations. Theresearch was conducted in a descriptive analytic form, with the following steps: (1) giving questions for the geometry reasoning test for SMP; (2) analyzing answers according to the criteria of reasoning; and (3) mapping students' answers to the results of the analysis according to the profile criteria. The data obtained were analyzed, and the results were described to illustrate the condition of the geometric reasoning abilities of elementary school students. Theresults obtained in this study were: (1) The Mastery of the concept of geometry in each junior high school/equivalent. The target with the acquisition of an average score from all schools was 55, which was quite low because there were some students who did not master the concept of geometry and there were other mathematical concepts related to solving test questions; (2) There was no significant difference in the mastery of geometry concepts for male or femalestudents for each SMP/equivalent target, except for one school, namely SMP Negeri 17, which was because males are superior to females in three questions with a difference in the percentage of numbers of significantly correct; (3) The mastery of geometry concepts in each junior high school. The target of studying each geometry material was considered good, except for question number 1 with the subject of the Pythagorean Theorem, because students were dominant in not being able to use the relationship between concepts, especially the operation ofthe compounding form and the roots.